DA’WA, MUSLIM MILLENNIALS AND SOCIAL MEDIA - Zulhazmi, Abraham Zakky; Hastuti, Dewi Ayu Sri (LENTERA, 2018)
The link between religion and cyberspace has become a necessity in the cyber era. The internet, in this case social media, changes many patterns and forms of communication. Social media has become a massive channel used by Indonesian preachers for the past decade or so. Da'wah on social media presents a number of challenges and opportunities, especially when dealing with millennials as majority users. This study intends to describe the phenomenon of da'wah on social media among millennial Muslims. This research is a descriptive qualitative research with literature study as a data collection method. The conclusion of this study is that there are three main points in viewing da'wa, millennial Muslims and social media. First, the character of millennial generation who tend to be out of the box and always connected to the internet more or less changes the da'wah landscape in Indonesia. They slowly leave the conventional da'wa, both in terms of theme and method choices. The popularity Hanan Attaki’s da’wah became one of the markers. Secondly, social media despite having a positive contribution to da'wah but also left a number of notes that demand attention, such as prejudice, easy spread of hate speech, reluctance to access primary sources and quality filter problems. Third, looking at millennial generations who have the characteristics of tolerance, pluralism and being able to appreciate diversity brings opportunities for the development of moderate Islamic da'wah in Indonesia. Keywords: da’wah, millenial, social media